2020
DOI: 10.1007/s00449-020-02440-3
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study on carboxylic acids production using bovine slaughterhouse wastewater: a promising substrate for resource recovery in biotechnological processes

Abstract: Carboxylic acids (CA) are considered high added-value compounds, and their production from wastes has gained economic and environmental notoriety. However, the CA production and kinetic modeling using some agro-industrial wastewaters, such as bovine slaughterhouse wastewater (SHW), are not well reported in the literature. Therefore, the objective of this work was to evaluate the CA production potential using SHW as a substrate under acidogenic conditions and to apply mathematical models to estimate the kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In further research, Morais et al (2021) and Coelho et al (2020a) also evaluated the prospecting of CAs from SHWs and RG, respectively, using the same operational conditions as their previous studies with SWs and DWs. For SHWs, the authors reported the conversion of 76% of COD to CAs (yield of 0.55 g acids per g COD), while for RG a yield of 0.62 g acids per g COD was obtained, corresponding to 82% conversion of applied organic matter.…”
Section: Production Of Carboxylic Acids From Anaerobic Treatment Of Agricultural and Agro-industrial Wastewatersmentioning
confidence: 99%
“…In further research, Morais et al (2021) and Coelho et al (2020a) also evaluated the prospecting of CAs from SHWs and RG, respectively, using the same operational conditions as their previous studies with SWs and DWs. For SHWs, the authors reported the conversion of 76% of COD to CAs (yield of 0.55 g acids per g COD), while for RG a yield of 0.62 g acids per g COD was obtained, corresponding to 82% conversion of applied organic matter.…”
Section: Production Of Carboxylic Acids From Anaerobic Treatment Of Agricultural and Agro-industrial Wastewatersmentioning
confidence: 99%